Sensation Seeking terhadap Kebahagiaan pada Wisatawan Domestik di Gunung Semeru - Fandi Rosi Sarwo Edi; Vita Nur Aini (Journal of Tourism and Creativity, 2021)
Happiness in life is the hope in the lives of many people with a sense of peace without suffering, which can be obtained in different ways. Sensation seeking is the need to find sensation and willingness to take risks that can be obtained through travel. Mount Semeru with a height of 3,676mdpl high in Java Island will have its own challenges for tourists who make the climb in search of sensation seeking as the final destination is happiness. The research aims to determine the effect of sensation seeking on happiness in domestic tourists on Mount Semeru. The subject of 120 domestic tourists was taken with incidental sampling techniques. Based on the results of a simple regression test obtained significance of 0.001 (0.001 < 0.05) and dihopetesis received. There is a sensation seeking influence on happiness in domestic tourists on Mount Semeru.